Hypertension school and inclusive posbindu: A community-based intervention model to reduce the burden of non-communicable diseases - Wihastuti, Titin Andri; Kartika, Annisa Wuri; Dewi, Elvira Sari; Hayati, Yati Sri; Indhiarti, Tantri Refa; Ardhia, Jessica Fio; Widiani, Luh; Arifah, Medisa Roro Putri Nur; Jannah, Riska Raudhatul; Amanda, Febrina; Indriyani, Damayanti; Machfud, Savinka Salsabiela Iriana; Tjahjono, Cholid Tri (Caring: Jurnal Pengabdian Masyarakat, 2025)
Non-communicable diseases (NCDs) such as hypertension are a major public health burden, particularly in rural areas with limited healthcare access. This community engagement program aimed to reduce the burden of NCDs through a comprehensive community-based intervention model involving the revitalization of inclusive Posbindu (integrated health posts) and the establishment of a Hypertension School. The intervention included cadre training, early risk screening, support group formation, and the application of a positive deviance approach. The results showed improved capacity of health cadres in hypertension detection and education, increased early screening in the productive age group, and enhanced self-management among patients. This model contributed to improved quality of life for hypertensive patients and better achievement of Minimum Service Standards (SPM) at the local health center. The integrative approach demonstrates significant potential in strengthening community-based health systems for sustainable NCD management.